2019
DOI: 10.1039/c9ta00781d
|View full text |Cite
|
Sign up to set email alerts
|

Ion-matching porous carbons with ultra-high surface area and superior energy storage performance for supercapacitors

Abstract: Polypyrrole (PPy)-derived porous carbons with an ion-matching micropore diameter exhibit ultra-high specific surface area and capacitance when used in supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Although the mixtures of ILs/organic solvents could reduce the viscosity and enhance durability in severe environments, this is not a universal strategy, and the wide electrochemical windows of ILs would be sacrificed. More recently, Zhang et al developed the porous carbons with high specific surface area and suitable micropore diameter to match IL ions (Zhang L. et al, 2019). They emphasized the importance of ion matching porous carbons in providing an ion highway for rapid ion transport to form more effective electric double layers, which resulted in superior performance (Figures 7E-G).…”
Section: Non-amphiphilic Il Electrolytesmentioning
confidence: 99%
“…Although the mixtures of ILs/organic solvents could reduce the viscosity and enhance durability in severe environments, this is not a universal strategy, and the wide electrochemical windows of ILs would be sacrificed. More recently, Zhang et al developed the porous carbons with high specific surface area and suitable micropore diameter to match IL ions (Zhang L. et al, 2019). They emphasized the importance of ion matching porous carbons in providing an ion highway for rapid ion transport to form more effective electric double layers, which resulted in superior performance (Figures 7E-G).…”
Section: Non-amphiphilic Il Electrolytesmentioning
confidence: 99%
“…The increase is more pronounced in the case of C–KOH sample, which is related to the exceptionally high surface area. Chemical activation of carbon materials leads to the formation of micropores, and it has been well demonstrated that the ion confinement in the micropores can lead to the higher capacitance [ 50 , 51 , 52 , 53 ]. The increase of the scan rate from 10 mV s −1 to 100 mV s −1 leads to the significant distortion of the CV curve shape and the essential decrease of capacitance values for C-non and C–CO 2 samples.…”
Section: Resultsmentioning
confidence: 99%
“…To further understand the textural properties of as‐prepared ACs, N 2 adsorption‐desorption isotherms and PSD (Figure and Table ). In the typical type I adsorption‐desorption isotherm of each AC, a sharp rise of nitrogen uptake at low relative pressure (P/P 0 < 0.05) is attributed to the existence of micropores (Figure a) . Moreover, the inconspicuous type H2 hysteresis loops of AC‐4‐550 and AC‐4‐650 at a high relative pressure (0.4‐1.0) are caused by their small amount of small mesopores .…”
Section: Resultsmentioning
confidence: 99%